Genome-wide annotation and functional identification of aphid GLUT-like sugar transporters - Price, Daniel RG (BioMed Central, 2014)
BACKGROUND: Phloem feeding insects, such as aphids, feed almost continuously on plant phloem sap, a liquid diet that contains high concentrations of sucrose (a disaccharide comprising of glucose and fructose). To access the available carbon, aphids hydrolyze sucrose in the gut lumen and transport its constituent monosaccharides, glucose and fructose. Although sugar transport plays a critical role in aphid nutrition, the molecular basis of sugar transport in aphids, and more generally across all insects, remains poorly characterized. Here, using the latest release of the pea aphid, Acyrthosiphon pisum, genome we provide an updated gene annotation and expression profile of putative sugar transporters. Finally, gut expressed sugar transporters are functionally expressed in yeast and screened for glucose and fructose transport activity. RESULTS: In this study, using a de novo approach, we identified 19 sugar porter (SP) family transporters in the A. pisum genome. Gene expression analysis, based on 214, 834 A. pisum expressed sequence tags, supports 17 sugar porter family transporters being actively expressed in adult female aphids. Further analysis, using quantitative PCR identifies 4 transporters, A. pisum sugar transporter 1, 3, 4 and 9 (ApST1, ApST3, ApST4 and ApST9) as highly expressed and/or enriched in gut tissue. When expressed in a Saccharomyces cerevisiae hexose transporter deletion mutant (strain EBY.VW4000), only ApST3 (previously characterized) and ApST4 (reported here) transport glucose and fructose resulting in functional rescue of the yeast mutant. Here we characterize ApST4, a 491 amino acid protein, with 12 predicted transmembrane regions, as a facilitative glucose/fructose transporter. Finally, phylogenetic reconstruction reveals that ApST4, and related, as yet uncharacterized insect transporters are phylogenetically closely related to human GLUT (SLC2A) class I facilitative glucose/fructose transporters. CONCLUSIONS: The gut enhanced expression of ApST4, and the transport specificity of its product is consistent with ApST4 functioning as a gut glucose/fructose transporter. Here, we hypothesize that both ApST3 (reported previously) and ApST4 (reported here) function at the gut interface to import glucose and fructose from the gut lumen. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2164-15-647) contains supplementary material, which is available to authorized users.